Elucidation of possible iron reduction mechanisms in kaolin bioleaching by bacillus species - Yong, Shih Nee (2023)
Kaolin minerals contain Fe impurities which affects its commercial value and refractory properties. Chemical treatments and physical techniques are able to remove these impurities but are associated with high environmental impact and cost. To circumvent these negative impacts, recent efforts have been focused on the use of bioleaching where kaolin is treated with microorganisms. Early results established a noticeable effect of the bacteria on the redox state of structural Fe, but knowledge gaps persist in terms of details on the bacterial-kaolin interactions such as electrostatic charges and bond formation during attachment of bacteria onto mineral surface. Moreover, information on the metabolites produced by bacteria and its effects on Fe(II)/Fe(III) ion equilibria in solution remains scarce. Hence, the ability and mechanisms of Bacillus sp. in Fe(III) reduction in kaolin bioleaching was studied. In this work, 20 g of kaolin powder with 9 x 108 CFU of Bacillus cereus, Bacillus aryabhattai and Bacillus megaterium were incubated in 200 mL of 10 g/L glucose medium respectively for 10 days at 30°C with 250 rpm. Based on phenanthroline results, all samples treated with bacteria showed increasing trends in Fe(III) reduction up until day 6 or 8 followed by a slight decrease towards the end of the ten-day period. For kaolin treated with B. cereus, the Fe(II) concentration increased gradually and had the highest extent of Fe(III) reduction at day 8, which is 1.43 µg/mL of Fe(II) in solution. Both of the kaolin treated with B. aryabhattai and B. megaterium reached a maximum of Fe(II) concentration at day 6, which were 1.26 µg/mL and 1.25 µg/mL respectively. Besides, EDS results showed the removal of Fe did not cause significant changes on chemical composition of other elements. Glucose concentration in the medium was shown to decrease progressively during bioleaching, an indication of glucose consumption by bacteria for cellular respiration. During the cell growth, B. cereus produced malate and acetate. For B. aryabhattai, malate, acetate, succinate, formate and lactate were detected whereas malate, acetate and lactate were produced by B. megaterium. The presence of organic acids was also confirmed by a decrease of pH values in the medium at the end of the bioleaching period. While the organic acids produced were responsible in reducing Fe(III) to Fe(II), SEM images showed bacterial activities damaged the edges of kaolin particles which appears to be sharper. However, XRD indicated that there was no formation of secondary mineral phases and no structural modification in kaolin was observed after bioleaching. In bacterial-kaolin interaction, FTIR test suggested that Bacillus sp. attached on the kaolin surfaces through the positive site of Fe(III) with OH (of the polysaccharides parts) of the EPS. The interaction of bacterial cells with kaolin surface altered the charge values of the solution which varies with pH value and bioleaching duration, confirmed by zeta potential measurements. In short, Bacillus sp. is shown to be able to reduce Fe(III) efficiently from kaolin. Although previous studies indicated the presence of organic acids during the bacterial growth, the concentrations of those acids have not been measured. Studies to date also did not specify mechanism of attachment of bacterial cell on kaolin surface in relation to production of acids and surface properties. In this study, a model involves attachment of bacterial cell on kaolin surface where positive Fe(III) site binds with OH (polysaccharide portion) of EPS through hydrogen bonding as well as production of organic acids by bacterial cell to reduce Fe(III) in kaolin to soluble Fe(II) in kaolin bioleaching by Bacillus species was proposed based on the surface, structural and chemical results obtained.